2008
DOI: 10.1111/j.1478-5153.2008.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic relationships in critical care nursing: a reflection on practice

Abstract: Using Titchen's Skilled Companionship Model as a guide as well as empirical and theoretical knowledge on nurse-patient relationships, this paper presents a reflection on a relationship that the author developed with a patient and his family encountered in her practice as a critical care nurse. REFLECTIVE CONCLUSIONS: Engaging in therapeutic nurse-patient relationships can expose nurses to emotional pain in the context of critical care nursing. The process of reflection can facilitate critical care nurses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 41 publications
1
40
0
1
Order By: Relevance
“…EI is considered meaningful for developing caring relationships (Akerjordet & Severinsson, 2004; McQueen, 2004; O'Connell, 2008) and for understanding patients' needs (Kooker, Schoultz, & Codier, 2007; McQueen, 2004), moods and emotions (Akerjordet & Severinsson, 2004; Freshwater & Strickley, 2004). EI is important during problem-solving, decision-making (Akerjordet & Severinsson, 2004; Freshwater & Strickley, 2004) and management of negative feelings for patients (McQueen, 2004; see also Sandgren, Thulesius, Fridlund, & Petersson, 2006).…”
mentioning
confidence: 99%
“…EI is considered meaningful for developing caring relationships (Akerjordet & Severinsson, 2004; McQueen, 2004; O'Connell, 2008) and for understanding patients' needs (Kooker, Schoultz, & Codier, 2007; McQueen, 2004), moods and emotions (Akerjordet & Severinsson, 2004; Freshwater & Strickley, 2004). EI is important during problem-solving, decision-making (Akerjordet & Severinsson, 2004; Freshwater & Strickley, 2004) and management of negative feelings for patients (McQueen, 2004; see also Sandgren, Thulesius, Fridlund, & Petersson, 2006).…”
mentioning
confidence: 99%
“…We have the knowledge about the patients that puts us in a position of power (O'Connell, 2008). Although it can be therapeutic to mutually exchange some information, only disclose enough to benefit the patient and family.…”
Section: Professional Boundariesmentioning
confidence: 99%
“…All relatives who participated in the GRAF confirmed the group's benefic effects, highlighting the importance of this care, both due to the opportunity of being heard, getting clarifications for their doubts and to the support from other participants, and also because they observed that they were not alone to face a situation that threatened with the disability or loss of a loved one. Their statements expressed the value of information, support and experiences shared with people going through similar situations, indicating that the group contributed to comply with their needs (6,8,11,17) .…”
Section: Discussionmentioning
confidence: 99%
“…For these people, more important than the strategy professionals use is to receive some kind of response to their needs (1,4,(12)(13)(14)17) . According to the study subjects' assessment, the support group was considered adequate for nursing care to these family members, because it allows them to feel cared for by someone who is concerned and willing to pay them some attention (4) .…”
Section: Discussionmentioning
confidence: 99%